Additive-free modified electrospray for fabricating smooth and highly permselective polyamide reverse osmosis membranes - Muhammad Ali Hasnain; Muhammad Mujahid; Long-Fei Ren; Jiahui Shao (Journal of Environmental Chemical Engineering, 2026)

Influence of chloride, sulphate, phosphate, and silicate-based potassium fertilizers and rice husk biochar on cadmium fate, complexation, leaching and uptake in maize under alkaline soil conditions - Muhammad Ashar Ayub; Muhammad Zia ur Rehman; Mujahid Ali; Muhammad Younas; Hesham F. Alharby; Ali Majrashi; Amnah M. Alamri; Amal A. M. Al-ghamdi (Biodegradation, 2026)

Cadmium Nanoparticles Disrupt Root Exosomal Defense Signaling Across Fruit & Root Crops: Mechanisms and Postharvest Rot Susceptibility - Qudrat Ullah; Waqas Haider; Muhammad Waqar; Abdul Rehman; Rashid Abbas Khan; Zaki ul Zaman Asam; Muhammad Zubair; Mujahid Farid (Plant Molecular Biology Reporter, 2026)

Inter-device interaction effects on turbine performance and blade loads in axially aligned tidal turbine arrays - Mujahid Badshah; Saeed Badshah; Sajjad Ahmad; Imtiaz Alam Shah; Zia Ur Rehman; Muhammad Amjad; Sakhi Jan (Ocean Engineering, 2026)

Phosphoric Acid Outperforms Diammonium Phosphate (DAP) in Cadmium Toxicity Alleviation by Decreasing Bioavailability and Optimizing Maize Physiology in Contaminated Alkaline Soil - Nadeem Sarwar; Mujahid; Muhammad Akhtar; Imtiaz Ahmed; Wajid Mahboob; Muhammad Imran Tipu; Muhammad Rashid Shaheen; Mashael Daghash Alqahtani; Usman Zulfiqar (Water, Air, & Soil Pollution, 2026)

Influence of inter-device spacing on performance and blade loads in staggered arrays of tidal current turbines - Mujahid Badshah; Saeed Badshah; Zia Ur Rehman; Sajjad Ahmad; Muhammad Amjad; Sakhi Jan; Imtiaz Alam Shah (Ocean Engineering, 2026)

Multi-scale modeling of habitat suitability and human-induced risk for the critically endangered white-rumped vulture (Gyps bengalensis) in South and Southeast Asia - Gulzaman William; Zafeer Saqib; Abdul Qadir; Ayesha Siddiqua; Zaki ul Zaman Asam; Mujahid Farid; Muhammad Jamshed Iqbal Chaudhry (The Science of Nature, 2026)

Nonlinear analysis of thermo-magneto slip flow of Jeffery fluid in a wavy curved channel - Maham Mujahid; Mounirah Areshi; Zaheer Abbas; Muhammad Yousuf Rafiq; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Microfacies and diagenetic synthesis of the late early-middle eocene Kirthar Formation, Waziristan, Pakistan: implications for reservoir characterization - Fawad Ahmed; Abdullah Khan; Nowrad Ali; Muhammad Zafar; Ihtisham-ul-Haq; Mujahid Ahmed Khan (Carbonates and Evaporites, 2026)

Synergistic effects of biochar and PGPR in enhancing the efficacy of biological control agents against Ganoderma boninense in oil palm (Elaeis guineensis L.): a critical review - Qudrat Ullah; Muhammad Zeshan; Waqas Haider; Muhammad Waqar; Zaki ul Zaman Asam; Muhammad Zubair; Mujahid Farid (Archives of Microbiology, 2026)

Effectiveness of treatments for propranolol toxicity: a systematic review of current approaches and evidence - Yafei Hu; Khizra Mujahid; Awais Ahsan; Anika Fatima; Inza; Maham Maqsood Ahmed; Maham Anoosh Butt; Sadia Younas; Muhammad Arif Aslam; Hafiz Muhammad Ahmad Javaid (European Journal of Clinical Pharmacology, 2026)

Corrigendum to “Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach” [J Hazard Mater 501 (2026) 14065] - Kashif Ali Memon; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach - Memon Kashif Ali; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

A novel hybrid MOF–metal oxide electrochemical sensor for ultra-trace detection of cadmium ions - Sabah Haider; Mujahid Mustaqeem; Maria Zaib; Mohammed Ashraf Gondal; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa (Journal of Environmental Chemical Engineering, 2025)

Optimizing tree crown density of finite coastal vegetation patches for enhanced tsunami mitigation - Fakhar Muhammad Abbas; Ali Abdullah Zaid Aldrees; Sohail Iqbal; Amina; Muhammad Atiq Ur Rehman Tariq; Naveed Anjum; Mujahid Iqbal; Usman Ghani; Ghufran Ahmed Pasha (Natural Hazards, 2025)

Dynamics of urinary tract infections: a comprehensive study on antimicrobial susceptibility, virulence profiling and molecular epidemiology of uropathogenic Escherichia coli from Pakistan - Zia Ashraf; Muhammad Hidayat Rasool; Bilal Aslam; Hasan Ejaz; Fatima Mujahid; Mohsin Khurshid (Molecular Biology Reports, 2025)

Monitoring and optimization of heavy metal phytoextraction in constructed wetlands amended with organic chelators - Mujahid Farid; Ambreen Mussarat; Muhammad Zubair; Zaki ul Zaman Asam; Ayesha Siddiqua; Wajiha Sarfraz; Roha Murtaza; Suliman Mohammed Suliman Alghanem; Haifa Abdul Aziz Sakit Alhaithloul (Environmental Monitoring and Assessment, 2025)

Influence of organic matter and mineral composition on carbonate source rock wettability: Implications for CO2 geostorage - Muhammad Usman; Nurudeen Yekeen; Muhammad Ali; Mujahid Ali; Alireza Keshavarz; Stefan Iglauer; Volker Vahrenkamp (Fuel, 2025)

Blue carbon management integrating socioeconomic and environmental interconnectivity in Southeast Asia: an urgent climate priority - Amani Becker; Sarah K. Bercovici; Jenny Choo; Fakhrurrozi Fakhrurrozi; Annabelle Fong; Sara E. Fowell; Emmy Hossain; Muhammad Ali Syed Hussein; Maryam Jamilah; Aazani Mujahid; Moritz Müller; Jillian Lean Sim Ooi; et al. (Frontiers in Marine Science, 2025)
This perspective article synthesises insights from a 2023 interdisciplinary workshop in Kuching, Malaysia, where 26 experts examined how land use and land cover change (LULCC) impacts Blue Carbon Ecosystems (BCE) in Southeast Asia (SEA) and identified pathways for integrated, science-informed governance. BCE in SEA (mangroves, seagrasses and tidal wetlands) are globally significant carbon sinks, critical to biodiversity and the livelihoods of millions, dependant on them for food, income and coastal protection. Yet rapid development and socio-economically driven LULCC threaten BCE resilience and carbon storage capacity. Blue Carbon initiatives risk falling short if they overlook the socio-ecological interconnectivity of these systems. Advances in remote sensing, sediment carbon accounting and ecosystem modelling have improved BCE monitoring, but key gaps persist. These include understanding cumulative upstream effects of LULCC on BCE carbon dynamics, integrating socio-economic with ecological data for robust scenario modelling and evaluating governance effectiveness and equity over time. We frame BCE as dynamic, interconnected socio-ecological systems and call for the advancement of systems thinking in coastal and climate policy. We underscore the need for transdisciplinary, nested governance models operating across ecological scales and political boundaries and argue for a systems-based management approach that links land-sea processes, addresses upstream-downstream dynamics and balances carbon market incentives with local needs. Recommendations include improved monitoring and carbon accounting; alignment between science and policy; regionally coordinated governance; and diversifying finance to reflect the full value of BCE beyond carbon. Together, these actions chart a path for resilient, science-based, socially inclusive BCE conservation in SEA.

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Engineered macrophages as versatile platforms for targeted cancer immunotherapy - Khizra Mujahid; Muhammad Arif Aslam; Jutaek Nam; Jeong Uk Choi (Journal of Pharmaceutical Investigation, 2025)

Standardization of Pruning in Dense, High Dense, and Ultra-High Dense Psidium guajava L. Orchards under Drip Irrigation - Mujahid Ali; Malik Muhammad Akram; Asif Iqbal; Muhammad Mohsan; Saqib Ayyub (Applied Fruit Science, 2025)

Harmonizing tourism and conservation through payment for ecosystem services: A case study of Gili Matra, Indonesia - Diswandi Diswandi; Luluk Fadliyanti; Mansur Afifi; Busaini Busaini; Muhammad Mujahid Dakwah (Environmental Development, 2025)

When low-dimensional nanomaterials meet polymers: A promising configuration for flame retardancy and corrosion protection - Salman Khalid; Muhammad Mubeen; Mohammad Tabish; Muhammad Jawad; Muhammad Uzair Malik; H.M. Ahsen Ilyas; Mubashar Mahmood; Mohammed Mujahid Alam; Jun Sun; Ghulam Yasin (Chemical Engineering Journal, 2025)

Molecular mechanisms and softening effects of edible acids on the intermuscular bones of grass carp (Ctenopharyngodon idella) - Mujahid Niaz; Muhammad Shahid; Noshaba Munawar; Zhihao Zhong; Shucheng Liu; Lianhong Guo; Jie Zhu (Food Chemistry, 2025)

Sustainable water desalination with anti-wetting Janus membranes under simulated industrial low-grade fluctuated heat conditions in DCMD - Muhammad Mujahid; Muhammad Ali Hasnain; Ghafoor Ahmad; Chao Wang; Fan Xiao; Zhe Wu; Long-Fei Ren; Jiahui Shao (Process Safety and Environmental Protection, 2025)

Paving the path to water security: The role of advanced adsorbents in wastewater treatment - Mushtaq Hussain; Asim Riaz; Hassan Zeb; Awais Ali; Rana Mujahid; Farooq Ahmad; Muhammad Shahzad Zafar (Journal of Water Process Engineering, 2025)

Enhancing phytoremediation in chamomile (Matricaria chamomilla L.) using moringa extract and zero-valent iron nanoparticles - Urooj Ansar Mughal; Mujahid Farid; Wajiha Sarfraz; Mostafa A. Abdel-Maksoud; Abdul Malik; Zaki ul Zaman Asam; Mohsin Abbas; Muhammad Zubair; Sabiha Fatima; Noreen Khalid (South African Journal of Botany, 2025)

A Novel Optimized Vibration-based Energy Harvester for Leak Detection in Wall-mounted Water Pipelines - Muhammad Faizan Mysorewala; Mati-Ur-Rasool Ashraf Virk; Mujahid Naqeebuddin Syed; Abdul-Wahid Saif; Lahouari Cheded; Saifullah Shafiq; Karim Sattar (Water Resources Management, 2025)

Seed priming with strigolactone GR24 develops tolerance toward salinity in ajwain (Trachyspermum ammi L.) by improving mineral nutrient contents and yield - Nazoora Mujahid; Muhammad Shahbaz (Acta Physiologiae Plantarum, 2024)

Hydrogen wettability of Saudi Arabian Basalt: Implications for H2 geo-storage - Muhammad Ali; Nurudeen Yekeen; Mujahid Ali; Amer Alanazi; Muhammad Shahzad Kamal; Alireza Keshavarz; Hussein Hoteit (Fuel, 2024)

Development of energy efficient flower-shaped defective TiO2 materials for wastewater remediation of agro-industries and oil refineries - Rab Nawaz; Marlia Mohd Hanafiah; Sajjad Haider; Muzammil Anjum; Mujahid Ali; Rawaiz Khan; Sammia Khurshid; Shafi Ullah; Muhammad Aqif; Adnan Haider; Zaher Abdel Baki (Process Safety and Environmental Protection, 2024)

The reversal of carbonate wettability via alumina nanofluids: Implications for hydrogen geological storage - Amer Alanazi; Mujahid Ali; Muhammad Ali; Alireza Keshavarz; Stefan Iglauer; Hussein Hoteit (Fuel, 2024)

Photovoltaic-integrated advancements for sustainable water production: Developing and evaluating an enhanced hybrid solar desalination system - Abubakar Sadiq Isah; Husna Bint Takaijudin; Balbir Singh Mahinder Singh; Tijani Oladoyin Abimbola; Muhammad Mujahid Muhammad; Sualawa Badruddeen Sani (Desalination, 2024)

High-throughput proteomic analysis of extracellular vesicles from saliva by chemical probe-based array - Ao Shen; Xin Feng; Dongxue Wang; Yuanyuan Liu; Kaifu Zhang; Jiliang Wang; Yanan Li; Muhammad Mujahid Ali; Lianghai Hu (Analytica Chimica Acta, 2024)

Treatment of marble industry wastewater by Brassica napus (L.) under oxalic acid amendment: efficacy as fodder and carcinogenic risk assessment - Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Ramzan Anwar; Mujahid Farid; Wajiha Sarfraz; Muhammad Zubair; Zaki Ul Zaman Asam; Mohsin Abbas; Muhammad Rizwan (Environmental Science and Pollution Research, 2024)

ANN and regression based quantification framework for climate change impact assessment on a weak transmission grid of a developing country across Horizon 2050 plus - M. Mahad Malik; Hamza Waheed Asim; Syed Ali Abbas Kazmi; Kamran Mujahid; Muhammad Waleed Ansari (Environment, Development and Sustainability, 2024)

The effect of methylene blue on stearic acid-aged quartz/CO2/brine wettability: Implications for CO2 geo-storage - Fatemah Alhammad; Mujahid Ali; Nurudeen Peter Yekeen; Muhammad Ali; Hussein Hoteit; Stefan Iglauer; Alireza Keshavarz (Gas Science and Engineering, 2024)

Oriented docking of the template for improved imprinting efficiency toward peptide with modifications - Juntao Zhou; Muhammad Mujahid Ali; Wenjing Yu; Xianhui Cheng; Yujun Gao; Lianghai Hu (Analytica Chimica Acta, 2024)

Optimised stacked machine learning algorithms for genomics and genetics disorder detection in the healthcare industry - Amjad Rehman; Muhammad Mujahid; Tanzila Saba; Gwanggil Jeon (Functional & Integrative Genomics, 2024)

Melatonin supplementation alleviates drought stress in peach (Prunus persica) seedlings by improving photosynthesis, root morphological traits, and antioxidant defense system - Shahid Iqbal; Faisal Hayat; Mujahid Hussain; Naveed Mushtaq; Muneer Rehman; Alaiha Asif; Ummara Khan; Muhammad Adnan Shahid (Acta Physiologiae Plantarum, 2024)

Recent outbreak of Marburg virus; a global health concern and future perspective - Usama Mujahid; Muhammad Ahmad; Attiqa Mujahid; Edward Narayan; Saif Ur Rehman; Hafiz M. N. Iqbal; Ishtiaq Ahmed (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Utilization of cereal-based husks to achieve sustainable development goals: Treatment of wastewater, biofuels, and biodegradable packaging - Syed Ali Hassan; Mueen Abbas; Waqar Mujahid; Waqar Ahmed; Saeed Ahmad; Abid Aslam Maan; Aamir Shehzad; Zuhaib F. Bhat; Rana Muhammad Aadil (Trends in Food Science & Technology, 2023)

The occurrence and probabilistic risk assessment of 3-MCPDEs and GEs in infant formulas from Chinese market employing Monte Carlo simulation technique - Zhengchao Shen; Kexin Tian; Muhammad Mujahid Ali; Sifan Mei; Xin Ma; Jiang Liang; Feng Pan; Jianwen Li; Haixia Sui; Zhenxia Du (Food and Chemical Toxicology, 2023)

Review of measurement of sustainable development goals: a comprehensive bibliometric and visualized analysis - Aaliyah Siddiqui; Shrirang Altekar; Pradeep Kautish; Sudhir Fulzele; Nirzar Kulkarni; Mujahid Siddiqui; Muhammad Farhan Bashir (Environmental Science and Pollution Research, 2023)

Impact of carbonate mineral heterogeneity on wettability alteration potential of surfactants - Ahmed AlZaabi; Muhammad Arif; Mujahid Ali; Ahmed Adila; Yawar Abbas; Ravi Shankar Kumar; Alireza Keshavarz; Stefan Iglauer (Fuel, 2023)

Modulations Induced by Seed Priming of Strigolactone (GR24) in Morpho-Physiological and Biochemical Attributes of Ajwain (Trachyspermum ammi L.) Under Salt Stress - Nazoora Mujahid; Muhammad Shahbaz; Aysha Kiran; Muhammad Ashfaq Wahid (Journal of Plant Growth Regulation, 2023)

Prediction and interpretation of antibiotic-resistance genes occurrence at recreational beaches using machine learning models - Sara Iftikhar; Asad Mustafa Karim; Aoun Murtaza Karim; Mujahid Aizaz Karim; Muhammad Aslam; Fazila Rubab; Sumera Kausar Malik; Jeong Eun Kwon; Imran Hussain; Esam I. Azhar; Se Chan Kang; Muhammad Yasir (Journal of Environmental Management, 2023)

Efficacy of marigold (Tagetes erecta L.) for the treatment of tannery and surgical industry wastewater under citric acid amendment: a lab scale study - Arooj Fatima; Mujahid Farid; Zaki Ul Zaman Asam; Muhammad Zubair; Sheharyaar Farid; Mohsin Abbas; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Study of the evolution of 3-MCPDEs and GEs in the infant formula production chain employing a modified indirect method based on magnetic solid phase extraction - Zhengchao Shen; Xin Ma; Muhammad Mujahid Ali; Jiang Liang; Haixia Sui; Zhenxia Du (Food Chemistry, 2023)

Magnetic susceptibilities of surface sediments from estuary rivers in volcanic regions - Abd Mujahid Hamdan; Kartika Hajar Kirana; Fathul Hakim; Muhammad Iksan; Satria Bijaksana; Mariyanto Mariyanto; Teuku Muhammad Ashari; La Ode Ngkoimani; Hadi Kurniawan; Aditya Pratama; Mulyadi Abdul Wahid (Environmental Monitoring and Assessment, 2022)

Citric acid enhanced phytoextraction of nickel (Ni) and alleviate Mentha piperita (L.) from Ni-induced physiological and biochemical damages - Kashaf Ul Khair; Mujahid Farid; Umair Ashraf; Muhammad Zubair; Muhammad Rizwan; Sheharyaar Farid; Hafiz Khuzama Ishaq; Usman Iftikhar; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Efficacy of Alternanthera bettzickiana to Remediate Copper and Cobalt Contaminated Soil Physiological and Biochemical Alterations - Amna Khalid; Mujahid Farid; Muhammad Zubair; Muhmmad Rizwan; Usman Iftikhar; Hafiz Khuzama Ishaq; Sheharyaar Farid; Urousa Latif; Kiran Hina; Shafaqat Ali (International Journal of Environmental Research, 2020)

Anticancer and antibacterial potential of Rhus punjabensis and CuO nanoparticles - Sania Naz; Saira Tabassum; Nelson Freitas Fernandes; Mohammad Mujahid; Muhammad Zia; Esperanza J. Carcache de Blanco (Natural Product Research, 2020)

Effect of tetramethyl thiuram disulfide (thiram) in relation to tibial dyschondroplasia in chickens - Hui Zhang; Khalid Mehmood; Xiong Jiang; Wangyuan Yao; Mujahid Iqbal; Muhammad Waqas; Mujeeb Ur Rehman; Aoyun Li; Yaoqin Shen; Jiakui Li (Environmental Science and Pollution Research, 2018)

Glutamic acid assisted phyto-management of silver-contaminated soils through sunflower; physiological and biochemical response - Mujahid Farid; Shafaqat Ali; Muhammad Zubair; Rashid Saeed; Muhammad Rizwan; Rasham Sallah-Ud-Din; Ahmad Azam; Rehman Ashraf; Wasim Ashraf (Environmental Science and Pollution Research, 2018)

Identification of pedilanthus leaf curl virus and associated betasatellite infecting turnip in Pakistan - Samrah Munir; Muhammad Khurshid; Hira Kanwal; Mujahid Hussain; Muhammad N. Sattar; Irfan Ali; Atiq-ur Rehman; Zafar Iqbal (Journal of Plant Pathology, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Spatial-temporal variations in surface ozone over Ushuaia and the Antarctic region: observations from in situ measurements, satellite data, and global models - Mohd Shahrul Mohd Nadzir; Matthew J. Ashfold; Md Firoz Khan; Andrew D. Robinson; Conor Bolas; Mohd Talib Latif; Benjamin M. Wallis; Mohammed Iqbal Mead; Haris Hafizal Abdul Hamid; Neil R. P. Harris; Zamzam Tuah Ahmad Ramly; Goh Thian Lai; et al. (Environmental Science and Pollution Research, 2018)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Microwave irradiation and citric acid assisted seed germination and phytoextraction of nickel (Ni) by Brassica napus L.: morpho-physiological and biochemical alterations under Ni stress - Mujahid Farid; Shafaqat Ali; Muhammad Rizwan; Rashid Saeed; Hafiz Muhammad Tauqeer; Rasham Sallah-Ud-Din; Ahmed Azam; Nighat Raza (Environmental Science and Pollution Research, 2017)

Citric acid enhanced the antioxidant defense system and chromium uptake by Lemna minor L. grown in hydroponics under Cr stress - Rasham Sallah-Ud-Din; Mujahid Farid; Rashid Saeed; Shafaqat Ali; Muhammad Rizwan; Hafiz Muhammad Tauqeer; Syed Asad Hussain Bukhari (Environmental Science and Pollution Research, 2017)

Phyto-management of Cr-contaminated soils by sunflower hybrids: physiological and biochemical response and metal extractability under Cr stress - Mujahid Farid; Shafaqat Ali; Nudrat Aisha Akram; Muhammad Rizwan; Farhat Abbas; Syed Asad Hussain Bukhari; Rashid Saeed (Environmental Science and Pollution Research, 2017)

Physiological and biochemical mechanisms of silicon-induced copper stress tolerance in cotton (Gossypium hirsutum L.) - Shafaqat Ali; Muhammad Rizwan; Najeeb Ullah; Saima Aslam Bharwana; Muhammad Waseem; Muhammad Ahsan Farooq; Ghulam Hasan Abbasi; Mujahid Farid (Acta Physiologiae Plantarum, 2016)

Mechanisms of silicon-mediated alleviation of drought and salt stress in plants: a review - Muhammad Rizwan; Shafaqat Ali; Muhammad Ibrahim; Mujahid Farid; Muhammad Adrees; Saima Aslam Bharwana; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Citric acid enhances the phytoextraction of chromium, plant growth, and photosynthesis by alleviating the oxidative damages in Brassica napus L. - Sehar Afshan; Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Farhat Abbas; Muhammad Ibrahim; Muhammad Aamer Mehmood; Ghulam Hasan Abbasi (Environmental Science and Pollution Research, 2015)

Alleviation of chromium toxicity by glycinebetaine is related to elevated antioxidant enzymes and suppressed chromium uptake and oxidative stress in wheat (Triticum aestivum L.) - Shafaqat Ali; Aaifa Chaudhary; Muhammad Rizwan; Hafiza Tania Anwar; Muhammad Adrees; Mujahid Farid; Muhammad Kashif Irshad; Tahir Hayat; Shakeel Ahmad Anjum (Environmental Science and Pollution Research, 2015)

Fulvic acid mediates chromium (Cr) tolerance in wheat (Triticum aestivum L.) through lowering of Cr uptake and improved antioxidant defense system - Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Sidra Kanwal; Qasim Ali; Muhammad Ibrahim; Rafaqat Ali Gill; Muhammad Daud Khan (Environmental Science and Pollution Research, 2015)

The effect of excess copper on growth and physiology of important food crops: a review - Muhammad Adrees; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Farhat Abbas; Mujahid Farid; Muhammad Zia-ur-Rehman; Muhammad Kashif Irshad; Saima Aslam Bharwana (Environmental Science and Pollution Research, 2015)

Silicon (Si) alleviates cotton (Gossypium hirsutum L.) from zinc (Zn) toxicity stress by limiting Zn uptake and oxidative damage - Shad Ali Anwaar; Shafaqat Ali; Skhawat Ali; Wajid Ishaque; Mujahid Farid; Muhammad Ahsan Farooq; Ullah Najeeb; Farhat Abbas; Muhammad Sharif (Environmental Science and Pollution Research, 2015)

EDTA enhanced plant growth, antioxidant defense system, and phytoextraction of copper by Brassica napus L. - Ume Habiba; Shafaqat Ali; Mujahid Farid; Muhammad Bilal Shakoor; Muhammad Rizwan; Muhammad Ibrahim; Ghulam Hasan Abbasi; Tahir Hayat; Basharat Ali (Environmental Science and Pollution Research, 2015)

EDTA ameliorates phytoextraction of lead and plant growth by reducing morphological and biochemical injuries in Brassica napus L. under lead stress - Urooj Kanwal; Shafaqat Ali; Muhammad Bilal Shakoor; Mujahid Farid; Sabir Hussain; Tahira Yasmeen; Muhammad Adrees; Saima Aslam Bharwana; Farhat Abbas (Environmental Science and Pollution Research, 2014)

Novel quinolyl-thienyl chalcones and their 2-pyrazoline derivatives with diverse substitution pattern as antileishmanial agents against Leishmania major - Syed Umar Farooq Rizvi; Hamid Latif Siddiqui; Muhammad Nisar Ahmad; Matloob Ahmad; Mujahid Hussain Bukhari (Medicinal Chemistry Research, 2012)